Simulation of thermal trigger design for crashworthiness structures - Peixinho, Nuno (2019)
This study presents an alternative approach for the improvement of crash energy absorption in representative automobile crashworthiness structures. It is studied the introduction of configurable crush initiators through localized heating in tubular structures. The main objective is to improve the ability to absorb impact energy in a progressive and controlled manner by a local modification of material properties. In this manner, associated with the softening of the aluminum alloy, the deformation can be introduced precisely, forcing the tubular structure to deform in a mode of high energy absorption and reducing the maximum load in a controlled manner. The application is studied on a representative geometry using numerical simulation.